The α-amylase and α-glucosidase inhibitory activities of the dichloromethane extracts and constituents of Ferulago bracteata roots - Songül Karakaya; Sefa Gözcü; Zühal Güvenalp; Hilal Özbek; Hafize Yuca; Benan Dursunoğlu; Cavit Kazaz; Ceyda Sibel Kılıç (Taylor & Francis Group, 2018)
Context: Ferulago (Apiaceae) species have been used since ancient times for the treatment of intestinal worms, hemorrhoids, and as a tonic, digestive, aphrodisiac, or sedative, as well as in salads or as a spice due to their special odors. Objectives: This study reports the α-amylase and α-glucosidase inhibitory activities of dichloromethane extract and bioactive compounds isolated from Ferulago bracteata Boiss. & Hausskn. roots. Materials and methods: The isolated compounds obtained from dichloromethane extract of Ferulago bracteata roots through bioassay-guided fractionation and isolation process were evaluated for their in vitro α-amylase and α-glucosidase inhibitory activities at 5000-400 µg/mL concentrations. Compound structures were elucidated by detailed analyses (NMR and MS). Results: A new coumarin, peucedanol-2'-benzoate (1), along with nine known ones, osthole (2), imperatorin (3), bergapten (4), prantschimgin (5), grandivitinol (6), suberosin (7), xanthotoxin (8), felamidin (9), umbelliferone (10), and a sterol mixture consisted of stigmasterol (11), β-sitosterol (12) was isolated from the roots of F. bracteata. Felamidin and suberosin showed significant α-glucosidase inhibitory activity (IC50 0.42 and 0.89 mg/mL, respectively) when compared to the reference standard acarbose (IC50 4.95 mg/mL). However, none of the tested extracts were found to be active on α-amylase inhibition. Discussion and conclusions: The present study demonstrated that among the compounds isolated from CH2Cl2 fraction of F. bracteata roots, coumarins were determined as the main chemical constituents of this fraction. This is the first report on isolation and characterization of the bioactive compounds from root extracts of F. bracteata and on their α-amylase and α-glucosidase inhibitory activities.